La ley natural y los bienes que perfeccionan a la persona. Completando la lista de la Summa Theologiae, I-II, q. 94, a. 2: aportación de Germain Grisez (2ª parte) - Antón LC, José María (Alpha Omega, 2011)
Having previously presented Grisez’s thought about the “basic human goods”, this present article critically examines Grisez’s position in a three-fold approach: discussing if pleasure can be a final reason for our actions; second, considering if the list of “basic human goods” is complete and exhaustive and finally, analyzing if, in the light of the “basic human goods theory’, contraception is really an act against life.